2022
DOI: 10.7759/cureus.24745
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Antenatal Eclampsia

Abstract: Most women who develop eclampsia have preceding preeclampsia (proteinuria and hypertension). This is especially true for otherwise healthy nulliparous women. However, recently, there has been a paradigm shift in this philosophy. There is mounting evidence that preeclampsia can develop even in the absence of proteinuria and hypertension and that eclampsia itself may be the initial manifestation of hypertensive disorder during pregnancy. We report a rare case of a 24-year-old primigravida at 30 weeks of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The literature contains additional case reports of atypical eclampsia (Table 2) in which the seizures were refractory to standard medical management 16–18 or in which they developed prior to 20 weeks' gestational age, 19,20 in the late postpartum period, 21–25 in the absence of proteinuria, 16,22,24,25 or in the absence of elevated blood pressures 17,21,22,24–28 . Eclampsia infrequently occurs without pre‐existing or subsequent hypertension, and our report adds to the limited number of such cases in the literature.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The literature contains additional case reports of atypical eclampsia (Table 2) in which the seizures were refractory to standard medical management 16–18 or in which they developed prior to 20 weeks' gestational age, 19,20 in the late postpartum period, 21–25 in the absence of proteinuria, 16,22,24,25 or in the absence of elevated blood pressures 17,21,22,24–28 . Eclampsia infrequently occurs without pre‐existing or subsequent hypertension, and our report adds to the limited number of such cases in the literature.…”
Section: Discussionmentioning
confidence: 77%
“…found that hypertension was absent in 16% of cases in a series of 399 women with eclampsia. To our knowledge, there have been fewer than 25 reported cases since then of atypical eclampsia in persistently normotensive patients, 17,21,22,[24][25][26][27][28] with only one of these cases occurring in the United States. 24 Among these normotensive patients with atypical eclampsia, only one had a reported abnormal transaminase value, with a slightly elevated AST of 66 U/L and a normal ALT of 35 U/L.…”
Section: Graves Andmentioning
confidence: 99%